2019
DOI: 10.4103/jips.jips_329_18
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effect of dentin surface treatment by air abrasion and Er:YAG laser on the retention of metal crowns luted with glass ionomer cement in teeth with reduced crown height: An in vitro study

Abstract: Aim and Objectives: The purpose of this study was to investigate the effect of dentin surface treatment with aluminum oxide air abrasion and Er:YAG laser on tensile bond strength of metal crowns. Metal crowns were luted with conventional glass ionomer cement (GIC) in the teeth with reduced crown height, where preparation geometry did not provide optimal retention form. Materials and Methods: Forty-eight human premolars were prepared to receive metal crowns and were rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Futhermore, similar studies have tested various surface conditioning methods to different restorative materials ( 35 , 36 , 37 ). Li et al ( 35 ) investigated lithium disilicate ceramics with two resin cements after thermocycling and revealed that HF acid etching combined with a silane showed the highest SBS values.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Futhermore, similar studies have tested various surface conditioning methods to different restorative materials ( 35 , 36 , 37 ). Li et al ( 35 ) investigated lithium disilicate ceramics with two resin cements after thermocycling and revealed that HF acid etching combined with a silane showed the highest SBS values.…”
Section: Discussionmentioning
confidence: 99%
“…Another study by Colombo et al ( 36 ) who also investigated the effects of surface pretreatments but on three diferent yttria-stabilized tetragonal zirconia polycrystalline ceramics presented that while air-borne particle abraded samples have reached the highest SBS values, the lowest values were obtained from the etched groups. Moreover, Chauhan et al ( 37 ) invastigated the effect of dentin surface treatment with aluminum oxide air abrasion and Er:YAG laser when bonding to metal crowns by using tensile bond strength test and found that Er:YAG laser treated dentin showed superior tensile bond strenght values when compared to untreated dentin and air abraded dentin.…”
Section: Discussionmentioning
confidence: 99%